2017
DOI: 10.1155/2017/8491383
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Dimorphism and Virulence: Molecular Mechanisms for Temperature Adaptation, Immune Evasion, and In Vivo Survival

Abstract: The thermally dimorphic fungi are a unique group of fungi within the Ascomycota phylum that respond to shifts in temperature by converting between hyphae (22–25°C) and yeast (37°C). This morphologic switch, known as the phase transition, defines the biology and lifestyle of these fungi. The conversion to yeast within healthy and immunocompromised mammalian hosts is essential for virulence. In the yeast phase, the thermally dimorphic fungi upregulate genes involved with subverting host immune defenses. This rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 88 publications
(113 reference statements)
0
38
0
5
Order By: Relevance
“…Paracoccidioides spp. are dimorphic fungi that change their morphology according to the environmental temperature, with a transition from mold at 25 • C to yeast at 37 • C in human lungs (San-Blas and Vernet, 1977;Gauthier, 2017). Although the primary route of PCM infection is pulmonary, the disease is frequently diagnosed by extensive, ulcerative and painful buccal manifestations corresponding to the clinical form of the multifocal type (Franco et al, 1987;Mendes et al, 2017;de Arruda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Paracoccidioides spp. are dimorphic fungi that change their morphology according to the environmental temperature, with a transition from mold at 25 • C to yeast at 37 • C in human lungs (San-Blas and Vernet, 1977;Gauthier, 2017). Although the primary route of PCM infection is pulmonary, the disease is frequently diagnosed by extensive, ulcerative and painful buccal manifestations corresponding to the clinical form of the multifocal type (Franco et al, 1987;Mendes et al, 2017;de Arruda et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from several pathogenic fungi have shown that morphology is linked with expression of virulence factors, colonization of the host, and evasion of host immune responses, etc (69, 70). The cnbR Δ mutants are significantly less virulent in a heterologous wax moth larva host model (27); however, it was not clear if the diminished virulence potential of cnbR Δ mutants was due to morphology, loss of the calcineurin, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of several pathogenic fungi have shown that morphology is linked with expression of virulence factors, colonization of the host, evasion of host immune responses, etc. (69,70). The cnbRΔ mutants were shown to be significantly less virulent in a heterologous wax moth larva host model (27); however, it was not clear if the diminished virulence potential of cnbRΔ mutants was due to morphology or loss of the calcineurin or both.…”
Section: A Novel Link Between Calcineurin and Byca An Amino Acid Permentioning
confidence: 99%